STUDENT RESPONSE TO HOAX NEWS ABOUT COVID-19 VACCINATION PROGRAM ON THE FACEBOOK - A. Rivai Beta; Sy. Nurul Shobah; Misnawati (Jurnal Scientia, 2022)
The high impact of Covid-19 made the government vaccination program. However, there was controversy over the Covid-19 vaccination. One of the reasons was the number of hoax news spread on Facebook. As intellectuals, students were led to give intelligent responses to Hoax news about Covid-19 vaccinations. This study aimed to determine student responses to the Hoax news of the covid-19 vaccination. The method used qualitative method. Data was collected by interviewing and observing ten students spread across four faculties of UIN Sultan Aji Muhammad Indris Samarinda. The criteria for students who are used as active students, have a Facebook account, and actively receive face news on the Covid-19 vaccination. Information obtained was then analyzed with the stages of reducing, grouping, analyzing, and concluding. The results were cognitive responses from Hoax news, such as the presence of a microchip, pork content, and can cause paralysis. Affective response, which creates fear and disbelief. Psychomotor response seeks the truth and thinks critically about the news before sharing it with the community through education.